Factors Influencing the Acceptability and Uptake of HIV Self-Testing Among Priority Populations in Sub-Saharan Africa: A Scoping Review - Felix Emeka Anyiam; Maureen Nokuthula Sibiya; Olanrewaju Oladimeji; Olanrewaju Oladimeji (Public Health Reviews)
ObjectivesTo identify and synthesize the factors influencing the acceptability and uptake of HIV self-testing (HIVST) among Priority Populations (PPs) in Sub-Saharan Africa (SSA) through a comprehensive scoping review.MethodsUsing Arksey and O'Malley’s framework refined by Levac, we systematically reviewed the literature on factors affecting HIVST uptake and acceptability among PPs in SSA. The review included searches in six databases (Embase, Medline (via Ovid), PubMed, PsycINFO, Web of Science, WHO Global Health Library), as well as grey literature, including (Google Scholar and OpenGrey), limiting publications to 2010–2023.ResultsThe review found evidence indicating that HIVST is widely accepted and considered convenient among priority groups. Key challenges include limited post-test counseling and linkage to care, which hinder effective implementation. Peer-led and digital distribution strategies show the potential to increase uptake. However, user errors and economic constraints pose significant barriers to scaling HIVST, underscoring the need for targeted interventions to address these implementation challenges for optimal impact.ConclusionWhile HIVST can boost testing rates among PPs in SSA, overcoming access and utilization barriers is crucial. Interventions addressing economic, educational, and systemic challenges are essential for successful HIVST integration into broader HIV prevention and care efforts.